The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1371/journal.pone.0167333
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Acute Radiation Sickness: A Feasibility Study in Non-Human Primates Circulating miRNAs for Triage in Radiological Events

Abstract: Development of biomarkers capable of estimating absorbed dose is critical for effective triage of affected individuals after radiological events. Levels of cell-free circulating miRNAs in plasma were compared for dose-response analysis in non-human primates (NHP) exposed to lethal (6.5 Gy) and sub-lethal (1 and 3 Gy) doses over a 7 day period. The doses and test time points were selected to mimic triage needs in the event of a mass casualty radiological event. Changes in miRNA abundance in irradiated animals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 57 publications
(66 reference statements)
2
37
0
Order By: Relevance
“…Plasma miR-150-5p levels were found to correlate well with lymphocyte and neutrophil depletion kinetics [122]. Also, miR-574-5p exhibited a dose-dependent increase 24 h post irradiation in NHPs with lethal versus sub-lethal exposure and returned to the baseline level by d 3.…”
Section: Biomarkers For Radiation Injury and Efficacy Of Radiationmentioning
confidence: 99%
“…Plasma miR-150-5p levels were found to correlate well with lymphocyte and neutrophil depletion kinetics [122]. Also, miR-574-5p exhibited a dose-dependent increase 24 h post irradiation in NHPs with lethal versus sub-lethal exposure and returned to the baseline level by d 3.…”
Section: Biomarkers For Radiation Injury and Efficacy Of Radiationmentioning
confidence: 99%
“…MiR-150-5p was identified as a circulating miRNA that correlated with delivered dose within a dose range of 1-12 Gy 24-48 h after irradiation. Due to its abundance in lymphocytes, miR-150-5p was proposed as a sensitive marker for lymphocyte depletion and BM damage and a useful bioindicator for radiation biodosimetry (Jacob et al 2013;Menon et al 2016). It was also reported that expression of miR-150-5p in exosomes secreted by non-small cell lung cancer cells and stromal cells decreased with radiation but increased intracellularly both in cancer cells and stromal cells, suggesting that exosomal export of these miRNAs may be downregulated in these cells in response to radiation (Dinh et al 2016;Menon et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…At higher radiation doses in the mouse (~10 Gy and above), damage resulting from radiation exposure can be observed in the GI system in addition to bone marrow, and weight loss; and diarrhea are typically observed, which can lead to dehydration and mortality 6 . There is an increasing traction about determining the role of serum miRNAs in responding to radiation, particularly in the context of biodosimetry 7,8 . A number of reviews highlighted the potential utility of miRNAs as predictors of carcinoma prognosis 9,10 and of drug efficacy 11,12 .…”
mentioning
confidence: 99%
“…Cross-species validated radiation marker for time-and dose-dependent reduction in expression in plasma8 . We found subsequent reduction in expressions in the Mid (−1.31) and Late phases (−1.53).…”
mentioning
confidence: 99%